Quantitative Analysis for Management, Global Edition - Render, Barry (Pearson International Content, 2023)
Quantitative Analysis for Management helps you develop a real-world understanding of business analytics, quantitative methods, and management science. It does this by using mathematical model building, tangible examples, and computer applications. You’re first introduced to models and then you apply those models using step-by-step, how-to instructions and software.